2018
DOI: 10.1186/s12992-018-0332-2
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Indigenous primary health care service delivery models: a systematic scoping review

Abstract: BackgroundIndigenous populations have poorer health outcomes compared to their non-Indigenous counterparts. The evolution of Indigenous primary health care services arose from mainstream health services being unable to adequately meet the needs of Indigenous communities and Indigenous peoples often being excluded and marginalised from mainstream health services. Part of the solution has been to establish Indigenous specific primary health care services, for and managed by Indigenous peoples. There are a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
182
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(194 citation statements)
references
References 77 publications
10
182
0
2
Order By: Relevance
“…Beyond the barriers relating to clinician knowledge and practice, key barriers in health systems include staffing problems and the health service model. Three recent reviews on the primary care for Aboriginal people with chronic disease echoed similar barriers to the optimal management of chronic disease, including high staff turnover, lack of dedicated chronic disease management staff to coordinate care, lack of specific chronic disease training for staff, lack of cultural security and demanding workloads …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the barriers relating to clinician knowledge and practice, key barriers in health systems include staffing problems and the health service model. Three recent reviews on the primary care for Aboriginal people with chronic disease echoed similar barriers to the optimal management of chronic disease, including high staff turnover, lack of dedicated chronic disease management staff to coordinate care, lack of specific chronic disease training for staff, lack of cultural security and demanding workloads …”
Section: Discussionmentioning
confidence: 99%
“…Three recent reviews on the primary care for Aboriginal people with chronic disease echoed similar barriers to the optimal management of chronic disease, including high staff turnover, lack of dedicated chronic disease management staff to coordinate care, lack of specific chronic disease training for staff, lack of cultural security and demanding workloads. [30][31][32] Service provision via a model of care that enables management of chronic lung disease and addresses the complex needs of Aboriginal families must include: (i) resources and staff dedicated to specific chronic lung disease detection and management according to protocols, including post-hospitalization follow-up for lower respiratory tract infections; (ii) trained and empowered AHW throughout the healthcare system; and (iii) health education to teach families about chronic lung disease. 30 A study limitation is the focus on one region; however, almost all doctors related their experiences to working in other rural and remote regions of Australia and overseas, suggesting that the study findings are generalizable to other regions.…”
mentioning
confidence: 99%
“…There is widespread agreement that for Aboriginal culture is at the heart of ACCHO practice and was present throughout most activities described in annual reports which is not surprising given the importance culture to the health and wellbeing of the community (p. 9) [24]. This evidence is supported by findings of a 2018 systematic review where culture was identified as underpinning all ACCHO practice [27], and the National Aboriginal and Torres health. Furthermore, we argue that culture and societal values, rather than being an independent socio-political factor, are the basis on which socio-political discourse and policies are built.…”
Section: Socio-economic and Political Contextmentioning
confidence: 95%
“…Improving the delivery of evidence-based preventive care requires broader investments in health service capacity and strong Indigenous participation in PHC centres, both of which are characterised by community-controlled services; an appropriate number of Aboriginal and Torres Strait Islander staff at all levels of the PHC service; the meaningful use of data to support quality of care and CQI; and investments in regional support structures and functions (Bailie et al 2017;Harfield et al 2018). Previous research has identified specific barriers to implementation of health assessments (Kehoe and Lovett 2008;Bailie et al 2013;Jennings et al 2014;Schütze et al 2016), and this provides useful guidance for developing targeted interventions to improve uptake of health assessments.…”
Section: Lesson 3 Indigenous Leadership and Strengthening Of Organismentioning
confidence: 99%